Arab and international issues in light of the secret People's Way newspaper 1962-1963 (documentary study) - Mohammad Ali, PhD Manaf Jaseb (Thi Qar Arts Journal, 2022)
The newspaper "Tareeq al shae'b " began to publish secretly، and it is the party's spokesman for the Iraqi Communist Party in November 1961. This newspaper practices publishing after it was banned in September 1961 and eight copies have been issued Seven copies were issued in 1962 as for The eighth edition is in January 1963The newspaper stopped publishing after the military coup on the eighth of February for a certain period of time  and then returned to publishing  again in secret way until 17 July, When the opinions of the political forces became convergent and compatible Baathist - communist forces With the National Front، it started to work clearly    The subject of the research dealt with the secret newspaper" Tareeq Al shae'b" , the way of the people، in its eight publications during the period between 1962 - 1963 And studying the contents, articles and positions of the special Arab and international issues of the  newspaper.The research was enhanced by adding appendices to all articlesfor the sake of scientific integrity and  to reach it in an easy way.